Identification of Alternative Polyadenylation in Cyanidioschyzon merolae Through Long-Read Sequencing of mRNA - Schärfen, Leonard; Zigackova, Dagmar; Reimer, Kirsten A.; Stark, Martha R.; Slat, Viktor A.; Francoeur, Nancy J.; Wells, Melissa L.; Zhou, Lecong; Blackshear, Perry J.; Neugebauer, Karla M.; Rader, Stephen D. (Frontiers in Genetics, 2022)
Alternative polyadenylation (APA) is widespread among metazoans and has been shown to have important impacts on mRNA stability and protein expression. Beyond a handful of well-studied organisms, however, its existence and consequences have not been well investigated. We therefore turned to the deep-branching red alga, Cyanidioschyzon merolae, to study the biology of polyadenylation in an organism highly diverged from humans and yeast. C. merolae is an acidothermophilic alga that lives in volcanic hot springs. It has a highly reduced genome (16.5 Mbp) and has lost all but 27 of its introns and much of its splicing machinery, suggesting that it has been under substantial pressure to simplify its RNA processing pathways. We used long-read sequencing to assess the key features of C. merolae mRNAs, including splicing status and polyadenylation cleavage site (PAS) usage. Splicing appears to be less efficient in C. merolae compared with yeast, flies, and mammalian cells. A high proportion of transcripts (63%) have at least two distinct PAS’s, and 34% appear to utilize 3 or more sites. The apparent polyadenylation signal UAAA is used in more than 90% of cases, in cells grown in both rich media or limiting nitrogen. Our documentation of APA for the first time in this non-model organism highlights its conservation and likely biological importance of this regulatory step in gene expression.